Identitas Lokal pada Penamaan “Jembatan Merah” dalam Karya Musik Keroncong - Muhammad Kusuma Wardhana (Mahesa Research Center, 2021)
This paper seeks to explain the term “Jembatan Merah” in Indonesia from a humanities perspective. Researchers see that the term which has become one of Indonesia's local identities contains many implied meanings rather than simply being understood as a form of denotation of a red bridge. Even the interpretation of this term in keroncong music works has contributed a lot in popularizing this term. Starting from the popularity of the Gesang keroncong music which uses the name